Both the nature of KIR3DL1 alleles and the KIR3DL1/S1 allele combination affect the KIR3DL1 NK‐cell repertoire in the French population. Issue 4 (4th March 2013) - Gagne, Katia; Willem, Catherine; Legrand, Nolwenn; Djaoud, Zakia; David, Gaëlle; Rettman, Pauline; Bressollette‐Bodin, Céline; Senitzer, David; Esbelin, Julie; Cesbron‐Gautier, Anne; Schneider, Thierry; Retière, Christelle
<x xml:space="preserve">Abstract</x> NK‐cell functions are regulated by many activating and inhibitory receptors including KIR3DL1. Extensive allelic polymorphism and variability in expression can directly alter NK‐cell phenotype and functions. Here we investigated the KIR3DL1+ NK‐cell repertoire, taking into account the allelic KIR3DL1/S1 polymorphism, KIR3DL1 phenotype, and function. All 109 studied individuals possessed at least one KIR3DL1 allele, with weak KIR3DL1*054, or null alleles being frequently present. In KIR3DL1high/null individuals, we observed a bimodal distribution of KIR3DL1+ NK cells identified by a different KIR3DL1 expression level and cell frequency regardless of a similar amount of both KIR3DL1 transcripts, HLA background, or KIR2D expression. However, this bimodal distribution can be explained by a functional selection following a hierarchy of KIR3DL1 receptors. The higher expression of KIR3DL1 observed on cord blood NK cells suggests the expression of the functional KIR3DL1*004 receptors. Thus, the low amplification of KIR3DL1high, KIR3DL1*004 NK‐cell subsets during development may be due to extensive signaling via these two receptors. Albeit in a nonexclusive manner, individual immunological experience may contribute to shaping the KIR3DL1 NK‐cell repertoire. Together, this study provides new insight into the mechanisms regulating the KIR3DL1 NK‐cell repertoire.